Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Asli Daerah di Provinsi Jawa Barat (2015-2024) - Mochammad Juvither Teguh Alfharizqi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study aims to analyze the influence of Gross Regional Domestic Product (GDP), Human Development Index (HDI), and Open Unemployment Rate (TPT) on Regional Original Income (PAD) in 27 Regencies/Cities of West Java Province for the 2015-2024 period. This study uses Population as a control variable to minimize regional scale bias. The research method used is a quantitative approach with panel data regression analysis techniques. Based on the results of the test using the Random Effect Model (REM), the study found that after controlling for population factors, the variables of GDP and HDI had a positive and significant effect on PAD. On the other hand, TPT does not have a significant influence on PAD in West Java Province. These results show that West Java's fiscal independence is highly dependent on economic productivity and the quality of human capital. The policy implications are directed at strengthening leading sectors and investing in the quality of human resources to optimize the regional tax base in a sustainable manner.